Unsecured Credit and the Social Safety Net in U.S. States - Rhodes, Alec P.; Norris, Davon; Houle, Jason; Dwyer, Rachel E.; Bruch, Sarah K.; Berger, Lawrence M. (American Sociological Review, 2026)
Low-income households in the United States draw on public and private resources to manage economic risk. Cross-national scholars describe a “credit–welfare state tradeoff” where credit markets become particularly important when state benefits are less supportive. The United States is frequently highlighted in this regard, with its often-inadequate market-first safety net. Both credit markets and the safety net are, however, highly unequal and segmented across U.S. states. We provide new empirical insights on the credit–welfare state nexus by leveraging a large national sample of credit record data that allows us to distinguish between credit instruments. We link these data to a comprehensive dataset on state safety nets with comparable measures of program supportiveness. We estimate two-way fixed-effects models that exploit temporal variation within states in safety net supportiveness. We find that living in states with more supportive safety nets is associated with a lower probability of high-cost alternative payday, installment, and personal finance loan use, and a higher probability of mainstream credit card access, particularly among low-income households. In the context of the relative inadequacy of the U.S. safety net, state safety net supportiveness matters less for whether people borrow than for what credit instruments they use. Our findings suggest that efforts to restrict the U.S. safety net are likely to increase reliance on high-cost loans among low-income households, furthering the unequal burden of interest and fees levied on these households.